2019
DOI: 10.1016/j.heliyon.2019.e01996
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of mitochondrial impairment in the pathogenesis of imatinib-induced renal injury

Abstract: Imatinib is a tyrosine kinase inhibitor widely administered against chronic myeloid leukemia. On the other hand, drug-induced kidney proximal tubular injury, electrolytes disturbances, and renal failure is a clinical complication associated with imatinib therapy. There is no precise cellular mechanism(s) for imatinib-induced renal injury. The current investigation aimed to evaluate the role of mitochondrial dysfunction and oxidative stress in the pathogenesis of imatinib nephrotoxicity. Rats received imatinib … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…Calcium antagonists [251][252][253][254][255] and ACE-inhibitors [256][257][258][259][260] reduced respiration and ATP synthesis. Sorafenib directly impaired mitochondrial function at clinically relevant concentrations [261] whereas imatinib lacked direct mitochondrial effects but affected mitochondrial functions via altered kinase and other signalling pathways [261,262]. Likewise, ciclosporin A, rapamycin, and tacrolimus did not directly induce mitochondrial dysfunction but decreased energy production [263,264].…”
Section: Conclusion and Open Questionsmentioning
confidence: 99%
“…Calcium antagonists [251][252][253][254][255] and ACE-inhibitors [256][257][258][259][260] reduced respiration and ATP synthesis. Sorafenib directly impaired mitochondrial function at clinically relevant concentrations [261] whereas imatinib lacked direct mitochondrial effects but affected mitochondrial functions via altered kinase and other signalling pathways [261,262]. Likewise, ciclosporin A, rapamycin, and tacrolimus did not directly induce mitochondrial dysfunction but decreased energy production [263,264].…”
Section: Conclusion and Open Questionsmentioning
confidence: 99%
“…A luciferase-luciferin-based kit (Enliten, Promega, Madison, WI) was used to measure mitochondrial ATP content [ 82 , 83 ]. Samples and buffer solutions were prepared based on the kit instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, 500 µl of mitochondrial samples (1 mg protein/ml) were treated with 100 µl of ice-cooled TCA solution (0.5% w/v in double-distilled water) and centrifuged (15,000 g, 15 min, 4°C). Afterward, 100 µl of ATP kit content was added to 100 µl of the supernatant (in the dark), and the luminescence intensity of samples was measured (λ = 560 nm using a FLUOstar Omega multifunctional microplate reader, BMG Labtech Inc., Germany) [ 83 ].…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have also shown that imatinib increases oxidative stress levels. 35,36 Based on our biochemical findings, although oxidative stress increased significantly in testis tissue in the Imatinib-20 group compared to the control group at TBARS measurements, we determined a decrease in the Imatinib-60 group. One study involving an induced hepatic fibrosis model reported a decrease in oxidative stress in a group receiving imatinib.…”
Section: Groupmentioning
confidence: 96%